Sistema contable para mejorar la gestión administrativa y financiera en la junta administradora de agua potable „‟ARROZ-UCO” del cantón Echeandia provincia Bolívar, año 2014 - Yolanda Amparito, Espín Carvajal (2015)
This paper aims graduation. Implement an accounting system in Drinking Water Management Board Rice-Uco Echeandía Canton Bolivar Province, to improve decision-making of managers. Today at present, for any commercial or service activity it is essential accounting because it reflects the economic and financial picture of what is currently in the moment that they will make decisions, whether operating investment and financing. The Administrative Board of Water Supply Rice-Uco, is a problem of how it affects the lack of an accounting system to improve administrative and financial management. This graduation work is divided into three chapters, the same as below. Chapter I the subject, background, problem formulation, justification, objectives, theoretical framework is divided in reference to the story of the Board, geo reference is the map where this institution is located is presented, the conceptual theory terminologies are used and applied within the Board, scientific framework definitions are taken from various sources, the same contributing to the scientific development of this graduate work. Here Chapter II refers to the analysis and interpretation of results, tabulation, presentation and interpretation of data, testing hypotheses, conclusions and recommendations. Chapter III The proposal is defined, it is based on the development of the chart of accounts to the financial statements that cast the actual data accurately and truthfully accounting data of the Board, they are for better decision-making in the Administrative Board of Water Supply Rice-Uco.